Estimation of prevalence of sarcopenia by using a new bioelectrical impedance analysis in Chinese community-dwelling elderly people. Issue 1 (December 2016) - Wang, Hui; Hai, Shan; Cao, Li; Zhou, Jianghua; Liu, Ping; Dong, Bi-Rong
Abstract Background The aim of the present study was to validate the usefulness of the new octapolar multifrequency bioelectrical impedance analysis (BIA) for assessment of appendicular skeletal muscle mass (ASM) by comparing it with that of dual-energy X-ray absorptiometry (DXA) and to investigate the prevalence of sarcopenia in Chinese community-dwelling elderly according to Asian Working Group for Sarcopenia (AWGS) definition. Methods A cross-sectional study was conducted in communities of Chengdu, China. A total of 944 community-dwelling elderly adults aged ≥60 years were included. ASM was measured by using DXA as a criterion method to validate a standing eight-electrode multifrequency BIA (InBody 720), followed by a further estimation of the prevalence of sarcopenia according the AWGS definition. Results In the Bland-Altman analysis, no significant difference was found between DXA and BIA based on the ASM measurements. The prevalence of AWGS-defined sarcopenia was 12.5% in the elderly women and 8.2% in the elderly men. Conclusions BIA is suitable for body composition monitoring (ASM) in elderly Chinese as a fast, noninvasive, and convenient method; therefore, it may be a better choice in large epidemiological studies in the Chinese population. The prevalence of AWGS-defined sarcopenia was approximately 10.4% and increased with age in the Chinese community-dwelling elderly in this study.